New mosquito species records (Diptera: Culicidae) from Singapore - Jeffery, J.; Lee, R.M.L.; Tan, S.Y.; Liew, C.; Ng, L.C.; Lam-Phua, S.G. (2010)
Nine species of mosquitoes in eight genera are recorded for the first time in Singapore. An additional two species were overlooked in a 1986 checklist for mosquitoes in Singapore, and one was described after 1986. Location and habitat data are provided for the nine new records. With the inclusion of these new records the number of species reported from Singapore is 137.